2017
DOI: 10.1038/s41598-017-12318-2
|View full text |Cite|
|
Sign up to set email alerts
|

Amplitude of travelling front as inferred from 14C predicts levels of genetic admixture among European early farmers

Abstract: Large radiocarbon datasets have been analysed statistically to identify, on the one hand, the dynamics and tempo of dispersal processes and, on the other, demographic change. This is particularly true for the spread of farming practices in Neolithic Europe. Here we combine the two approaches and apply them to a new, extensive dataset of 14,535 radiocarbon dates for the Mesolithic and Neolithic periods across the Near East and Europe. The results indicate three distinct demographic regimes: one observed in or a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
64
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 62 publications
(68 citation statements)
references
References 69 publications
4
64
0
Order By: Relevance
“…BP mirror divergent rates in Neolithisation and agricultural land use, as previously suggested by discrete charcoal data (Robin and Nelle, 2014). CHAR composites allow determination of the spatial spread of human fire usage in prehistoric and historic agrarian land management, which was previously described using archaeological compilations (Feeser and Dörfler, 2015;Poska et al, 2004;Silva and Vander Linden, 2017) and quantitative land cover reconstructions (Marquer et al, 2017;Trondman et al, 2015).…”
Section: Fire As An Agrarian Land Management Toolmentioning
confidence: 73%
See 1 more Smart Citation
“…BP mirror divergent rates in Neolithisation and agricultural land use, as previously suggested by discrete charcoal data (Robin and Nelle, 2014). CHAR composites allow determination of the spatial spread of human fire usage in prehistoric and historic agrarian land management, which was previously described using archaeological compilations (Feeser and Dörfler, 2015;Poska et al, 2004;Silva and Vander Linden, 2017) and quantitative land cover reconstructions (Marquer et al, 2017;Trondman et al, 2015).…”
Section: Fire As An Agrarian Land Management Toolmentioning
confidence: 73%
“…The degree of intentional forest disturbance and use of forest resources probably varied in space and time (Meadows et al, 2016;Poska and Saarse, 2002;Wacnik et al, 2011;Zvelebil, 2008) and in relation to access to other resources from, e.g., rivers, the sea, or early contacts with sedentary cultures (Krause-Kyora et al, 2013;Silva and Vander Linden, 2017). For example, new analytical approaches in archaeology suggest that Mesolithic forest-based diets were reduced in favor of waterbased diets in the Baltic hinterland (Meadows et al, 2016).…”
Section: Fire Use By Hunter-gatherersmentioning
confidence: 99%
“…A plethora of radiocarbon-dated sites showing early evidence of farming have allowed archaeologists to model how this cultural innovation spread throughout Europe in the Neolithic. Consistently across studies, researchers have observed that the expansion of farming was broadly two-pronged, consisting of two cultural movements which can be broadly associated with the Impressa / Cardial Ware and Linear Pottery archaeological horizons [25][26][27][28][29] . Now, the new abundance of radiocarbon-dated ancient genomes allows us to trace how genetic ancestry spread as a consequence of this cultural transformation 14,30 .…”
Section: Techno-cultural Development and Diffusionmentioning
confidence: 68%
“…Since the distribution of samples is often patchy, geostatistical techniques such as kriging and splines are used to spatially interpolate the information in order to provide quantitative estimates of the timing of spread. Work carried out in Europe (Bocquet-Appel et al, 2009), Asia (Silva et al, 2015), and Africa (Russell et al, 2014) demonstrates that there are different rates of diffusion even within a region, reflecting the possible impact of natural features (e.g. waterways, elevation, ecology) on diffusion rates (Davison et al, 2006;Silva and Steele, 2014).…”
Section: Date Of First Agriculturementioning
confidence: 99%